Isolasi Mikroba Dari Air Asam Tambang Pada Area Pertambangan Tembaga Di Pulau Wetar, Provinsi Maluku - Male, Yusthinus T.; Modok, Deddy W.S.; Seumahu, Cecilia A.; Malle, Dominggus (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2019)
This research was conducted to find bacteria from the genus Acidithiobacillus ferrooxidans which isolated from mine acid water in the copper mining area on Wetar Island, Maluku Province. This bacterium will be utilized in the biohidrometallurgical process (bioleaching) for copper extraction in mining area. The results of this study indicate that bacteria can be isolated from mine acid water samples by enrichment method that was use liquid media from Leathen which is optimized using Trypton Soya Broth (TSB) and bacterial growth on solid media. The presence of Thiobacillussp bacteria was confirmed by the results of gene analysis using a 16S rRNA sequence showing the presence of mixed bacterial colonies but not a single colony.